2017
DOI: 10.1519/jsc.0000000000001571
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of Wearable Activity Trackers Under Free-Living Conditions

Abstract: Brooke, SM, An, H-S, Kang, S-K, Noble, JM, Berg, KE, and Lee, J-M. Concurrent validity of wearable activity trackers under free-living conditions. J Strength Cond Res 31(4): 1097-1106, 2017-The purpose of this study is to evaluate the concurrent validity of wearable activity trackers in energy expenditure (EE) and sleep period time (SPT) under free-living conditions. Ninety-five (28.5 ± 9.8 years) healthy men (n = 34) and women (n = 61) participated in this study. The total EE and SPT were measured using 8 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 18 publications
2
60
0
1
Order By: Relevance
“…These devices have been shown to have accuracy comparable to commercial actigraphy systems. 6,7 We hypothesized that residents get less sleep on call nights, and even less on nights when they subsequently report they feel too fatigued to perform their duties safely. We also hypothesized that residents would sleep less with increasing call volume, and that the difference would be larger for pages about unfamiliar patients.…”
Section: Introductionmentioning
confidence: 99%
“…These devices have been shown to have accuracy comparable to commercial actigraphy systems. 6,7 We hypothesized that residents get less sleep on call nights, and even less on nights when they subsequently report they feel too fatigued to perform their duties safely. We also hypothesized that residents would sleep less with increasing call volume, and that the difference would be larger for pages about unfamiliar patients.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite navigation on cell-phones allows precise walking/running track recording, etc. There are numerous (commercial) activity trackers available which are validated by multiple studies [82][83][84][85][86] such as the SenseWear armband ® (BodyMedia Inc., Pittsburgh, PA, USA), Fitbit ® (Fitbit Inc., San Francisco, CA, USA), Garmin activity trackers (Garmin, Olathe, KS, USA), Jawbone (San Francisco, CA, USA), and many more. Although recent research showed that all these monitors did have error ranges in free-living conditions [82][83][84], it is also suggested that these activity trackers can offer an opportunity to stimulate health, fitness, and quality of life [82,87], particularly when used for consumer-based self-monitoring to encourage behavioral changes [85].…”
Section: Pa Monitoring and Stimulation (10/23)mentioning
confidence: 99%
“…There are numerous (commercial) activity trackers available which are validated by multiple studies [82][83][84][85][86] such as the SenseWear armband ® (BodyMedia Inc., Pittsburgh, PA, USA), Fitbit ® (Fitbit Inc., San Francisco, CA, USA), Garmin activity trackers (Garmin, Olathe, KS, USA), Jawbone (San Francisco, CA, USA), and many more. Although recent research showed that all these monitors did have error ranges in free-living conditions [82][83][84], it is also suggested that these activity trackers can offer an opportunity to stimulate health, fitness, and quality of life [82,87], particularly when used for consumer-based self-monitoring to encourage behavioral changes [85]. Various studies have used and validated activity trackers to measure PA in both healthy controls [88,89] and CKD patients [90][91][92] and showed that this objective measure is more accurate than self-reported PA by questionnaires, which often over-or underestimates a patients' PA level [93].…”
Section: Pa Monitoring and Stimulation (10/23)mentioning
confidence: 99%
“…Introduction Wearable activity trackers are increasingly incorporated into daily life and are advancing in their technology in means of accuracy, validity and acceptability, [1][2][3][4][5][6] however there is deficient knowledge on using these devices in a paediatric setting. The objective of this pilot study was to assess the feasibility of physical activity tracking in children 7 before and after a standardized surgical intervention and to assess the recovery time after surgery.…”
mentioning
confidence: 99%